2010
DOI: 10.2522/ptj.20090383
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Promotion in the Physical Therapy Setting: Perspectives From Practitioners and Students

Abstract: Physical therapist practice appears to be an excellent avenue for promoting a physically active lifestyle and could potentially play an important public health role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
122
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(151 citation statements)
references
References 22 publications
21
122
1
7
Order By: Relevance
“…According to the specialists [23] in the medical and motric education field, the most important objective is the development and diversification of prevention activities.…”
Section: Introductionmentioning
confidence: 99%
“…According to the specialists [23] in the medical and motric education field, the most important objective is the development and diversification of prevention activities.…”
Section: Introductionmentioning
confidence: 99%
“…A sample size of 200 was set to detect a significant correlation of 0.2 or greater (power = 0.8; significance = 0.05) [20] between variables. This was calculated on sampling Physiotherapy courses with an average final-year cohort of fifty students and a response rate of 30% based on the work of others [17]. Other studies have reported response rates to questionnaire as low as 12% [15].…”
Section: Methodsmentioning
confidence: 99%
“…The survey was adapted from a study of physical activity promotion in Australian physiotherapists and physiotherapy students [17]. Permission was granted to adapt and use the survey by the correspondence author.…”
Section: A U T H O R C O P Ymentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies observed general medical practitioners [8][9][10][11] with only a limited number of studies giving specific attention to other health professionals such as dietitians [12], nurses [8,13] pharmacists [14], physiotherapists [15] and clinical psychologists [16,17]. These studies have given insights into the practice behaviors and receptiveness to physical activity promotion of each profession along with the feasibility and practicality of physical activity promotion within each professional setting.…”
Section: Introductionmentioning
confidence: 99%